2014
DOI: 10.3109/02713683.2014.915575
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Photopic Negative Response of Multifocal Electroretinogram in Patients with Glaucoma

Abstract: These results suggest that the N2 component of the slow-sequence mfERGs is affected by glaucoma in the central retinal area. Regional variations in the contribution of the retinal ganglion cell activity to the N2 should be considered when examining the mfERGs in glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 29 publications
2
35
1
3
Order By: Relevance
“…The observed differences between the focal macular and full-field PhNRs indicate that functional contribution of the inner retina including the RGCs is greater in the focal macular ERG than in the full-field ERG in monkeys. Therefore, our results support the idea that the PhNR elicited from the macula is advantageous for detection of macular RGC dysfunction, consistent with recent studies [14,20].…”
Section: Discussionsupporting
confidence: 93%
“…The observed differences between the focal macular and full-field PhNRs indicate that functional contribution of the inner retina including the RGCs is greater in the focal macular ERG than in the full-field ERG in monkeys. Therefore, our results support the idea that the PhNR elicited from the macula is advantageous for detection of macular RGC dysfunction, consistent with recent studies [14,20].…”
Section: Discussionsupporting
confidence: 93%
“…1–4 As an objective clinical measure of neuroretinal function, this component has been used primarily to evaluate eyes with glaucoma, 5–13 although studies have also investigated its changes in retinal vascular diseases, 1416 conditions causing optic atrophy, 1721 and following vitreoretinal surgery. 22 Despite its potential clinical use for these conditions, a major impediment to its widespread and routine application is the difficulty of its implementation in clinical settings and its large magnitude of measurement variability.…”
Section: Introductionmentioning
confidence: 99%
“…The three modes selected were mfERG, ff-ERG and PERG because they have each been evaluated extensively and proven effective in clinical studies of human glaucoma [19,21,13,14,22,23,20,24,15] as well as in previous laboratory studies in NHP eyes after retinal ganglion cell or optic nerve injury [34,28], including EG [35–39,17,40,41,2931]. To our knowledge, however, no prior study has compared all three modes in the same cohort of glaucomatous eyes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the mfERG N2 component is analogous to the PhNR of the ff-ERG [Viswanathan S, et al IOVS 2009;50: ARVO E-Abstract 4758], which in turn may share retinal generators with the PERG N95 [38,56]. Thus it is not surprising that the mfERG N2 appears to reflect glaucomatous damage [23,57,58]. Significant reduction of LFC amplitudes in mfERG responses to a more complicated stimulus have also been reported in NHP EG [41], which might reflect a similar underlying functional abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation